2005
DOI: 10.4081/ijas.2005.2s.386
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and IGF-1 in goat milk: influence of the diet

Abstract: Plasma IGF-1 and insulin have both growth-related and anabolic actions. The anabolic role of plasma IGF-1 consists of stimulating the uptake of amino acids and glucose by the cells, with an action similar to that of insulin. The main regulation of plasma IGF-1 and insulin is associated with food intake, especially with energy and protein intake. Moreover, insulin modulates peripheral satiety signals and directly targets the central nervous system to inhibit food intake (Sparks et al., 2003; Gale et al., 2004)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
4
6
1
Order By: Relevance
“…Dietary treatment did not significantly affect plasma INS levels, although they have been previously correlated with energy intake in adult goats (Magistrelli et al, 2005;Todini et al, 2007b). The correlation between INS levels and the adiposity state, previously reported in sheep (Archer et al, Dietary supplement, mohair and hormones in Angora kids 2002) was confirmed in the present study, where plasma INS was positively correlated with LW and BCS.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Dietary treatment did not significantly affect plasma INS levels, although they have been previously correlated with energy intake in adult goats (Magistrelli et al, 2005;Todini et al, 2007b). The correlation between INS levels and the adiposity state, previously reported in sheep (Archer et al, Dietary supplement, mohair and hormones in Angora kids 2002) was confirmed in the present study, where plasma INS was positively correlated with LW and BCS.…”
Section: Discussionsupporting
confidence: 86%
“…Circulating levels of total IGF-1 were not different between the two groups, while a positive correlation with the level of nutrition was previously reported in sheep (Bass et al, 1991;Adams et al, 2000;Pittroff et al, 2006) and goats (Magistrelli et al, 2005). It is noteworthy that dietary supplementations, with soybean, failed to induce a rise in plasma INS and IGF-1 in Merino rams, an effect which was observed with cowpea and lupin (Blache et al, 1996).…”
Section: Discussionsupporting
confidence: 53%
“…In this study, the IGF-1 level (between 42.13 and 91.08 ng/mL) measured in the pasture group with higher milk yield compared to the pen group (pasture group 283.73 kg, pen group 184.37 kg; P < 0.001) was higher than the milk IGF-1 level in the pen group (between 30.78 and 52.42 ng/mL). The finding that milk IGF-1 level changed based on feeding systems is consistent with the findings of Magistrelli et al (38). In addition, the blood IGF-1 level (41.7 ng/mL) identified in Saanen goats (35) was found to be similar to the milk IGF-1 level (between 30.78 and 52.42 ng/mL) of the pen group, and it was similar to or higher than that of the pasture group (between 42.13 and 91.08 ng/mL).…”
Section: Igf-1supporting
confidence: 91%
“…In this process, IGF-1 plays an important role in almost all tissue and organ cell proliferation with its metabolic impact on growth and development pathways (36). While it was reported that IGF-1 had no relationship in pigs with lactation milk yield (37), the studies on goats identified relationships between both blood and milk plasma IGF-1 levels and milk yield (35,38). In this study, the IGF-1 level (between 42.13 and 91.08 ng/mL) measured in the pasture group with higher milk yield compared to the pen group (pasture group 283.73 kg, pen group 184.37 kg; P < 0.001) was higher than the milk IGF-1 level in the pen group (between 30.78 and 52.42 ng/mL).…”
Section: Igf-1mentioning
confidence: 99%
“…The lack of difference in insulin concentration between the two diets in both species is in contrast to previous studies, where high-starch diets increased insulin concentration, compared to low-starch diets in Saanen goats [ 30 ] and in Sarda ewes [ 5 ]. The higher insulin concentration observed in sheep than goats suggests that the former had a metabolic status more inclined toward an anabolic pathway than the latter and confirmed the inverse relationship between insulin and milk production level [ 31 ].…”
Section: Discussioncontrasting
confidence: 97%